Misogyny, Racism, and Islamophobia: Street Harassment at the Intersections. (December 2019) - Mason-Bish, Hannah; Zempi, Irene
Veiled Muslim women are at an increased risk of street harassment in the current political and economic climate. Their visibility, combined with their popular portrayal as culturally dangerous or threatening means that they are vulnerable to receiving verbal and physical threats, which can be misogynistic and Islamophobic in nature. Drawing on 60 individual and 20 focus group interviews with Muslim women in the United Kingdom who wear the niqab (face veil) and had experienced harassment in public, this qualitative study details their lived experiences. It argues that an intersectional analysis is crucial to understanding the nuances of their lived experiences and the impact street harassment has on their lives. The findings demonstrate that street harassment can produce a hostile environment for veiled Muslim women, which can have a terrorizing effect, limiting their full participation in the public sphere.